TI_GERICHTE 52.2010.453 vom 25. Februar 2011 , Rilascio di un permesso di dimora per ballerine extra CE/AELS - TI Tribunale d'appello (2011)
Rilascio di un permesso di dimora per ballerine extra CE/AELS